Identification and Computational Analysis of Novel TYR and SLC45A2 Gene Mutations in Pakistani Families With Identical Non-syndromic Oculocutaneous Albinism - Bibi, Nousheen (Front Genet, 2020)
Non-syndromic oculocutaneous albinism (nsOCA) is an inherited disorder of melanin biosynthesis with autosomal recessive mode of inheritance, presenting either hypopigmented or depigmented skin, hair, and eyes. It is genetically heterogeneous with seven loci (OCA1–OCA7) reported to date. In the present study, we have reported three consanguineous families (A, B, C) presenting identical nsOCA phenotypes. Sanger sequencing revealed a novel [NM_000372.5: c.826 T > C, p.(Cys276Arg)] and a recurrent variant [NM_000372.5: c.832C > T, p.(Arg278(∗))] in tyrosinase (TYR) in families A and B, respectively. Microsatellite marker-based homozygosity mapping linked family C to OCA4. Sequence analysis identified a novel insertion variant (NM_016180.5: c.1331_1332insA) in the SLC45A2. Further, in silico mutagenesis and dynamic simulation approaches revealed that a novel Cys276Arg variant abolished the cysteine bridge and might contribute toward decreased stability of the TYR protein. Our study expands the mutation spectrum of the TYR and SLC45A2 genes and emphasizes that molecular investigations are essential for accurate disease diagnosis.